# calculus

log (3x-9) = 2log3 - log27+ log(x+3)

Solving the euqation using the properties of logarithms

How do you do this?

1. 👍
2. 👎
3. 👁
1. I will assume that all logs have the same base.

log(3x -9) = log [3^2*(x+3)/(3^3]
= log[(x+3)/3]

Therefore
3x -9 = (x+3)/3
9x -27 = x +3
8x = 30
x = 3.75

Check:
log (3x -9) = log 2.25 = 0.35218

2log3 -log27 + log(6.75)
= 0.95424 -1.43136 + 0.82930
= 0.35218

It makes no difference what log base you choose, as long as it is the same for all terms. (I chose base 10 when checking)

1. 👍
2. 👎

## Similar Questions

1. ### Trigonometry

This is a logs question If u=x/y^2, which expression is equivalent to log u? 1) log x + 2 log y 2) 2(log x- log y) 3) 2(log x + log y) 4) log x- 2 log y

2. ### Trigonometry

The expression log(x^n/ radical y)is equivalent to 1. n log x - 1/2 log y 2. n log x- 2 log y 3. log (nx) - log (1/2y) 4. log (nx) - log (2y)

1) use the properties of logarithms to simplify the logarithmic expression. log base 10 (9/300) log - log 300 log 9 = 2 log 3 log 300 = log 3 + log 100 = log 3+2 I just do not know how to put these together now!

4. ### pre calculous

use the properties of logarithms to write the expression as a sum or difference of logarithms or multiples of logarithms. show your work ln x^2/y^3 Assuming x,y AND z are positive use properties of logariths to write the

1. ### Math

If ln a=2, ln b=3, and ln c=5, evaluate the following: (a) ln(a^−2/b^4c^−3)= -.9524 (b) ln(√b^−4*c^1*a^−1)= -1.739 (c) ln(a^2b^4)/ln(bc)^−2= 42.39 (d) (ln(c^−1))*(ln(a/b^3))^−4= -.03507 I am getting these answers

2. ### Math

Find the exact solution, using common logarithms, and a two-decimal-place approximation of each solution. log(7x + 4) = 2 + log(2x − 3) Solve the equation. log(x^3) = (log x)^2

3. ### Algebra 2

How is the expression log 32 - log 8 written as a single logarithm? log 4 log 8 log 24 log 40

4. ### math

Calculate without using tables or calculators log 450 and log 324 given log 2 =0.3010 and log 3 =0.4771

1. ### Math/trig

Log radical b/ a^2 is equivalent to 1) 1/2 log b + 1/2 log a 2) l/2 log b- 2 log a 3) 2 log b - 1/2 log a 4) 1/2logb/2 log a

2. ### logarithm functions

use the properties of logarithms to expand the expression as sum, difference or multiple of logarithms. Simplify. a.log(x^3/2) b.log base4 16a

3. ### Math

Use the properties of logarithms to rewrite and simplify the logarithmic expression. 1.) log(9/300) 2.) log2(4^2 x 3^4)

4. ### calculus

If u = log(r), where r^2 = (x-a)^2 + (y-b)^2, and (x-1) and (y-b) are not zero simultaneously, show that d^2u/dx^2 + d^2u/dy^2 = 0. I first used some of the properties of log and made u = 1/2 * log((x-a)^2 + (y-b)^2) Then made u =